Effectiveness of Oral Misoprostol to Prevent Postcesarean Section Urinary Retention - Mahadika, Febrinata; Fauzi, Amir; Mirani, Putri; Theodorus, Theodorus (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: to determine the effect of misoprostol on the incidence of urinary retention in post cesarean section patients by measuring maternal residual urine volume 6 hours after catheter removal. Methods: This was a single-blind randomized controlled trial, at Department of Obstetrics and Gynecology Mohammad Hoesin Palembang Hospital from October 2016 to February 2017. Samples were patients who underwent cesarean section, either elective or emergencies treated at Department of Obstetrics and Gynecology Hospital, Mohammad Hoesin Palembang. Subjects were allocated into two groups: treatment group (receiving misoprostol) and placebo group. Urinary retention is diagnosed if post-voiding residual urine volume after Foley catheter removal was > 200 ml. Statistical analysis was performed using SPSS 17.0 Results: There were no differences in mean time between of urination between control group (placebo) and 600μg oral misoprostol group. The average of urine volume, and residual urine volume between control group (placebo) and 600μg oral misoprostol group was significantly different. 600μg misoprostol orally can increase the amount of urine and reduce the volume of urinary residue after cesarean section. Conclusion: 600μg oral misoprostol can increase urine volume and reduce volume of residual urine post cesarean section Keywords: Misoprostol, urinary retention, cesarean section   Tujuan: untuk mengetahui pengaruh misoprostol terhadap kejadian retensi urin pada pasien operasi seksio sesaria dengan mengukur volume residu urin maternal 6 jam setelah kateter dilepaskan. Metode: Penelitian uji klinik acak berpembanding (Randomized Controlled Trial) secara single blind (tersamar tunggal) ini dilakukan di Departemen Obstetri dan Ginekologi RSUP Mohammad Hoesin Palembang mulai bulan Oktober 2016 sampai dengan Februari 2017. Sampel penelitian adalah semua pasien seksio sesaria, baik elektif maupun emergensi yang dirawat di Departemen Obstetri dan Ginekologi RSUP Mohammad Hoesin Palembang. Subjek dialokasikan menjadi 2 kelompok yaitu kelompok penanganan yang menerima misoprostol dan kelompok placebo. Retensio urin didiagnosis jika volume residu urin pasca berkemih setelah kateter Foley dilepaskan >200 ml. Analisis statistik dilakukan dengan menggunakan SPSS 17.0 Hasil:Tidak terdapat perbedaan rerata waktu urinasi antara kelompok kontrol (plasebo) dengan misoprostol peroral 600µg.Terdapat perbedaan rerata jumlah urine, dan volume residu urine antara kelompok kontrol (plasebo) dengan misoprostol peroral 600µg. Misoprostol per oral 600µg dapat meningkatkan jumlah urin dan mengurangi volume residu urin pasca persalian seksio sesaria. Kesimpulan:. Misoprostol per oral 600µg dapat meningkatkan jumlah urin dan mengurangi volume residu urin pasca persalian seksio sesaria Kata kunci: Misoprostol, retensio urin, seksio sesaria